Political Ideology and Judicial Decision-Making in Contemporary Legal Systems - Fahira, Siti Hafsah; Nendi, Ikhsan; Hidayat, Agus Rohmat; Nurjanah, Aisyah; Santika, Rani (Journal of Law and Social Politics, 2024)
Background: Constitutional protection of minority rights remains a fundamental issue in contemporary constitutional law, particularly in the context of increasing political polarization, public health crises, and democratic backsliding. Although constitutions formally guarantee equality and non-discrimination, the effectiveness of these protections varies significantly across jurisdictions and minority groups. Objective: This study aims to examine comparative constitutional frameworks across regions and to identify the most effective constitutional mechanisms, judicial practices, and implementation challenges affecting religious, ethnic, LGBTQ+, linguistic, and other minority groups. Methods: This research employs a comparative legal analysis based on a systematic review of 25 Scopus-indexed publications published between 2019 and 2024. The analysis covers constitutional provisions, judicial decisions, and enforcement mechanisms from jurisdictions in Europe, the Americas, Asia, Africa, and Oceania. Results: The findings indicate that constitutional courts are the most effective mechanism for protecting minority rights, with an average effectiveness rate of 85%, outperforming legislative and administrative mechanisms. European jurisdictions demonstrate the highest level of protection, while African jurisdictions show comparatively lower effectiveness. Religious minorities constitute the largest proportion of constitutional cases, followed by ethnic minorities and LGBTQ+ groups. Non-discrimination principles show the strongest implementation, whereas political representation mechanisms remain the weakest. Conclusion: The study concludes that strong constitutional courts and robust non-discrimination principles are central to effective minority rights protection. However, enforcement gaps, political resistance, and limited institutional capacity continue to hinder the realization of constitutional guarantees, indicating the need for targeted institutional and policy reforms.